2006
DOI: 10.1634/stemcells.2005-0547
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Transdifferentiation Potential of Muscle‐Derived Stem Cells Propagated as Myospheres

Abstract: We have isolated from mouse skeletal muscle a subpopulation of slow adherent myogenic cells that can proliferate for at least several months as suspended clusters of cells (myospheres). In the appropriate conditions, the myospheres adhere to the plate, spread out, and form a monolayer of MyoD ؉ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 57 publications
3
71
0
Order By: Relevance
“…MuStem cells were able to expand in suspension, an experimental condition that does not support proliferation of differentiated cells that rapidly die. 69 In this original proliferation context, MuStem cells gave rise to large clusters of rounded cells termed myospheres, which have been also described for cells freshly isolated from mice 41 and human 70 skeletal muscle.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…MuStem cells were able to expand in suspension, an experimental condition that does not support proliferation of differentiated cells that rapidly die. 69 In this original proliferation context, MuStem cells gave rise to large clusters of rounded cells termed myospheres, which have been also described for cells freshly isolated from mice 41 and human 70 skeletal muscle.…”
Section: Discussionmentioning
confidence: 91%
“…39,40 More recently, studies confirmed that adult skeletal muscle contains nonadherent stem cells that are capable in vivo to contribute to the repair of injured muscle. 41,42 Unfortunately, the potential of MDSCs isolated as nonadherent populations for cell therapy has only been tested in the mdx model, 43 which exhibits limited clinical features and little or no endomysial fibrosis 44 when compared to DMD patients.…”
mentioning
confidence: 99%
“…The preplate technique, which is used to isolate cells according to variations in adhesion ability among different cell populations, [12][13][14][15]20,21 , showed different , and possessed a high myogenic potential both in vitro and in vivo, but could not undergo long-term self-renewal. Conversely, the LacZ-negative population, which possessed the ability to undergo long-term expansion, was highly positive for the stem cell markers CD34 (74.7%) and Sca-1 (98%; 74.5% Sca-1/CD34 doublepositive) and could not undergo myogenic differentiation in vitro and in vivo unless transduced with a retrovirus to express Pax7.…”
Section: Discussionmentioning
confidence: 99%
“…3 Our laboratory, as well as others, have shown that the slowly adhering cells (SACs) appear to be less committed to the myogenic lineage than fast-adhering cells. 3,[12][13][14][15] Following a preplate technique, only fast-adhering populations were obtained from Pax7 lacZ/lacZ mice. Furthermore, MDSC-like cells, which usually appear in the slowly adhering population in wild-type animals, appeared in our earlier preplate fractions from Pax7 lacZ/lacZ mice.…”
Section: Myogenic Cells Can Be Isolated From Pax7-deficient Skeletal mentioning
confidence: 99%
“…Other researchers called MDSC the side population cells isolated from skeletal muscle [112]. Others, a subpopulation of slow adherent cells derived from mouse skeletal muscle that can proliferate for months as myospheres [113].…”
Section: Muscle-derived Stem Cells (Mdsc)mentioning
confidence: 99%